Conformational Analysis And Vibrational Spectroscopic Studies On Dapsone - AKYÜZ, SEVİM; ILDIZ, GÜLCE ÖĞRÜÇ (Maik Nauka/Interperiodica/Springer, 233 Spring St, New York, Ny 10013-1578 Usa, 2012)
In this study, the theoretical conformation analysis of free dapsone has been performed by single point energy calculations at both semi-empirical PM3 and DFT/B3LYP-3-21G theory levels and three stable conformers were determined. Both the IR and Raman spectra of the molecule in solid phase have been recorded. The IR intensities and harmonic vibrational wavenumbers of each conformer were calculated by DFT method at B3LYP/6-31++G(d,p) theory level. For the fundamental characterization, the total energy distribution (TED) calculations of the vibrational modes were done using parallel quantum mechanic solution program (SQM) and the fundamental modes were assigned. The theoretical results are in agreement with the experimental ones.